Research trends related to Beluntas (Pluchea indica L.) in Indonesia during and post covid-19 based on scopus database - Donowarti, Idiek (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
This study aims to analyze important trends and information (findings) regarding Pluchea indica research in Indonesia during and after Covid-19 based on the Scopus Database. This research uses a systematic literature review (SLR) by adapting Moher's version of the PRISMA model to find the right articles. An interesting finding from this SLR is that the publication trend of Pluchea indica tends to increase in 2022-2024 even though the data ignores other types of publications (such as reviews, conference articles, chapters, books, and editorials, and in 2024 it is still ongoing so it is very likely that the number of articles will increase in end of year. There are several universities that are prominent in Pluchea indica research. Many universities in Indonesia are starting to be interested in focusing their research on Pluchea indica, in total, not per university and red) in the Scimago Journal & Country Rank. This shows that there have been no research articles on Pluchea indica that have made it into reputable journals or been included in major publishers. Eleven articles show that Pluchea indica, especially its leaves, have various medicinal properties and can be used in daily medical practice. days. Pluchea indica also has a connection or potential if it is associated with COVID-19.